(untitled) (Journal of the College of Basic Education, 2022)
The research of “The Doctrine of Contemporary Atheism ((its causes, divisions, means, treatment)) included an introduction and three sections. The first topic was: in the definition of atheism, and its causes, so I mentioned in the first requirement: the definition of atheism in language and terminology, and the second requirement was in: the causes of atheism Doctrinally and intellectually, and the second topic was in: Doctrines and Means of Atheism, and it was from two demands, the first in: Sections of Atheism and its doctrines, and the second requirement on: Means of Contemporary Atheism. I mentioned it, and I tried to find out about the subject through extensive research with the correct information.Research problem: the prevalence of the doctrine of atheism, religion, extremism, and whore by accepting deviant and forbidden acts in the Islamic community largely without deterring such ideas. The importance of the topic and the reason for choosing it: The necessity of knowing God, the Mighty and Sublime, with the right to know His Names and Attributes, to reconstruct the heart and the mind by believing in His Oneness, and singularity in worship, and the necessity to refute salt with the argument and The proof of the verse: (alm seen to the Haj Ibrahim in his Lord God grant him the king, as Abraham said, my Lord who gives life and Yamit said I salute Amit Abraham said, God comes the sun from the east, ’Bring them from Morocco were amazed that Kafr God does not guide the people Zalim) Objectives of the research and its hypotheses: The research aims to invalidate the semi-atheists, correct their false belief, and belief in God, through purposeful arguments according to sound frameworks that confirm the invalidity of the atheism doctrine. Methodological in the research: The research mentions the verses of the Noble Qur’an and some honorable hadiths that show the invalidity of the atheism doctrine, in addition to some sources that pertain to the subject of atheism. Theoretical framework and previous studies: After researching and tracing on the subject of atheism, I found a number of researches that were preceded by specialists in writing. He walks away from the beliefs and ideas that they took from atheists.